Zhongguo lishi gushi. sui qing - Mi, Weiwei (Zhangchun : Bei fang fu nü er tong chu ban she, 2017)
The contents of this book include: Yang Jian, Emperor Yang, Yang Guangqi, Sui Emperor Tour Jiangdu, Wagang Army Uprising, Taiyuan Qibing, Xuanwu Men's Change, Zhenguanzhizhi, Xuanzang Jingjing and so on.
In simplified Chinese script.
Keywords: Chinese literature -- China; Children's stories -- China; Historical story -- China